Neue Impulse zur sozialgeographischen Umstrukturierung nach der Verselbstständigung Sloweniens 1991 - Klemenčič, Vladimir (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
In the last decade after Slovenia became independent state and started to become gradually included in socio-economic system of European Union, we could follow changes in the structure of active population, especially decrease in the numbers of employed in industries and increase in the numbers of employed in tertiary and quartary sector. Increase of forests and social "prelog" also on the land which could be used for farming according to its natural character.
Keywords: agrarna geografija; demografski razvoj; družbene spremembe; družbeni procesi; ekonomski razvoj; podeželje; prebivalstvo; raba tal; rural area; Slovenia; Slovenija; socialna geografija